Competency based human resource management: A practitioner`s Handbook - Roy, Anindya Basu; Ray, Sumati (London Routledge Taylor and Francis group, 2025)
This book balances theory and illustrations to elucidate the application of competency modeling across varied industry domains. The book provides a methodology for developing reliable and valid psychometric tools for assessment. The book elaborately covers two most popular approaches assessment center and 360-degree assessment along with their pros and cons and most importantly insights on which approach to apply where. This book will help readers gain conceptual as well as practical insights into competency modeling, competency assessment and the integration of competency models into Human Resource Management (HRM).